EXAM ANXIETY, ACADEMIC BURNOUT, AND CHEATING BEHAVIOR AN EMPIRICAL STUDY OF UNDERGRADUATES IN ENUGU STATE - Cynthia, Ihekweme Nkechi (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
The current study examined whether exam anxiety and academic burnout would predict the variation in students' cheating behavior. It was expected that exam anxiety and academic burnout would significantly contribute to the variations in cheating behavior. Participants were 233 undergraduates enrolled in public tertiary institutions in Enugu State, Nigeria. They completed a self-report measure of cheating behavior, the cognitive test anxiety scale, and the academic burnout scale. A cross-sectional design was employed in the study. Data from the respondents were analyzed using the statistical package for social sciences (SPSS, Version 23). Multiple regression was performed to test the main hypotheses that exam anxiety and academic burnout would predict cheating behavior. The analysis showed that exam anxiety and academic burnout statistically significantly predicted cheating behavior, F (2, 231) = 31.25, p < 0.05. All two variables added statistically significantly to the prediction, p < .05. The result indicates that the predictor variables contributed 13.4% of the variance in the attitude towards statistics. The result has implications for academic integrity and provides crucial data for research.